Tin-antimony alloy and 3D printing method thereof

Through SLM technology, directly prepare tin alloy from SN fans and SB powder, and use layer -by -layer printing methods and specific printing parameters to solve the problem of insufficient Skyba alloy mechanical performance, realize high density, hardness, and tensile resistance. The improvement of intensity enhances friction and wear.

CN119368723APending Publication Date: 2025-01-28HUANGHE S & T COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411331476.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The mechanical and other comprehensive properties of existing 3D printed tin-based babbitt alloys need to be improved, especially because antimony has a low boiling point and is prone to evaporation, forming pores, and the solid solubility of antimony in tin is low, making it difficult to form fine and diffuse hard materials. Mutually.

Method used

Use the selection laser melting (SLM) technology directly from SN powder and SB powder to prepare tin 锑 alloys. Through layers of printing methods, the angle of scanning paths between the inter -layer scanning path is 10 ° ~ 30 °, and different printing on the surface under the forming parts is used under the surface of the form. Parameters to avoid the substrate hanging tin.

Benefits of technology

The high density, improvement and tensile strength of tin cricket alloys are realized, the friction and wear performance is enhanced, and the mechanical performance requirements of the tin shaft tile alloy on the axis material are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368723A_ABST
    Figure CN119368723A_ABST
Patent Text Reader

Abstract

The invention relates to a tin-antimony alloy and a 3D printing method thereof.The 3D printing method comprises the steps that layer-by-layer printing is conducted according to a three-dimensional model of a formed part, and mixed powder composed of Sn powder and Sb powder is used for layer-by-layer printing; the layer-by-layer scanning angle of the layer-by-layer printing is executed according to an interlayer scanning path included angle of 10-30 degrees except an area which cannot be selected; according to the tin-antimony alloy 3D printing method, the Sn powder and the Sb powder are directly used as raw materials for 3D printing of the tin-antimony alloy, the procedure of preparing tin-antimony alloy powder is avoided, and the problem that when input energy is too high, the mechanical property is reduced due to the fact that a Cu6Sn5 phase grows too much can be effectively solved; in addition, the layer-by-layer scanning angles are set to be different, so that anisotropy of tensile strength of the formed part in different directions due to a single scanning angle can be avoided; and meanwhile, the tin-antimony alloy disclosed by the invention has an excellent microstructure, so that the problem that the comprehensive properties such as mechanical properties of the existing 3D printing tin-based babbitt metal need to be improved is fundamentally solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of 3D printing technology, and specifically to a 3D printing method of tin-antimony alloy. Background Art

[0002] In recent years, 3D printing technology has developed rapidly in the exploration of new material preparation processes. Currently, the commonly used technology for metal additive manufacturing is selective laser melting (SLM). Due to the forming principle and forming characteristics of SLM technology, SLM alloys have excellent performance. For metal parts with complex structures and high precision requirements, three-dimensional forming can be directly performed. At present, SLM technology is widely used in high-temperature metals, such as titanium alloys, stainless steel, and aluminum alloys. For low-temperature alloys, SLM technology is mainly used in magnesium alloys.

[0003] With the rapid development of industry, the transmission equipment of downstream industries such as metallurgy, energy and transportation is developing in the direction of large-scale, heavy-load and high-speed. The large-scale machinery requires higher performance of sliding bearings. Different sliding bearing materials have different properties such as friction reduction, wear resistance, embedding, anti-seizure, etc., so their selection will affect the bearing's load capacity, limit temperature, starting performance and other indicators, and play a decisive role in the operating life of the bearing. Since 2000, the research and development of bearing materials has been rapid, and technical methods such as casting, spraying, welding, electroplating, sputtering and laser have been continuously updated.

[0004] Tin-based bearing alloys are often used as bearing alloys in large bearings because of their excellent wear resistance. Existing research on the preparation of tin-based bearing alloys using SLM technology still has many technical difficulties, such as: tin alloy powder is easy to oxidize, antimony has a low boiling point of 1860K, and is easy to evaporate during the forming process, forming more pores. The solid solubility of antimony in tin is low at 3.57at.%, and it is not easy to form a fine and dispersed hard phase. Due to these technical difficulties, at present, the research on the preparation of tin-based bearing alloys using SLM technology is still in its infancy. In existing research, the tin-based bearing alloys using 3D printing technology include tin-based babbitt alloys, such as ZSnSb11Cu6, etc., but the tensile strength of the tin-based babbitt alloy in different directions is anisotropic. When the input energy is too high, the Cu6Sn5 phase will grow too large, resulting in problems such as decreased mechanical properties. The friction and wear properties, hardness and strength of common cast tin-based bearing alloys also need to be improved. Summary of the invention

[0005] In view of this, the present invention provides a tin-antimony alloy and a 3D printing method thereof, so as to solve the problem that the comprehensive properties such as mechanics of the current 3D printed tin-based babbitt alloy need to be improved.

[0006] To achieve the above-mentioned object of the invention, in a first aspect, the 3D printing method of tin-antimony alloy disclosed in the present invention comprises:

[0007] Printing layer by layer according to the three-dimensional model of the formed part, wherein the layer by layer printing uses a mixed powder composed of Sn powder and Sb powder;

[0008] The layer-by-layer scanning angle of the layer-by-layer printing is performed according to the layer-by-layer scanning path angle of 10° to 30°, except for the area that cannot be selected.

[0009] In the present disclosure and possible embodiments, the particle size of the mixed powder is 15 μm to 50 μm, wherein more than 95% of the powder particles are spherical or quasi-spherical; and / or,

[0010] The content of the Sb powder in the mixed powder is 15%wt, and the rest is the Sn powder; and / or,

[0011] The Sn powder and the Sb powder are vacuum dried respectively and then vacuum mechanically mixed to obtain the mixed powder.

[0012] In the present disclosure and possible embodiments, the order of layer-by-layer printing is to first perform powder printing on the lower surface of the molded part in contact with the substrate, and then perform powder printing on the main body and upper surface of the molded part.

[0013] In the present disclosure and possible embodiments, the lower surface is 4-6 layers, and the upper surface is 4-6 layers and is laser remelted;

[0014] The inter-layer scanning path angle is 20°.

[0015] In the present disclosure and possible embodiments, the printing parameters for powder printing on the lower surface are set to 80W laser power, 0.2m / s scanning rate, 20μm layer thickness, 50μm scanning interval, and short straight line scanning strategy;

[0016] The printing parameters for powder printing on the main body and upper surface of the formed part are set as follows: laser power of 40-60 W, scanning rate of 0.3-0.7 m / s, layer thickness of 40 μm, scanning spacing of 80 μm, and scanning strategy of short straight line.

[0017] In the present disclosure and possible embodiments, the layer-by-layer printing is performed using a selective laser melting technology.

[0018] In the present disclosure and possible embodiments, the method of printing layer by layer according to the three-dimensional model of the formed part includes:

[0019] The three-dimensional model of the molded part is sliced, the molded part is laid out in a printing device into which an inert gas is introduced, and powder printing is performed according to the slice data and layout position of the three-dimensional model of the molded part.

[0020] In the present disclosure and possible embodiments, when performing the powder printing, the forming cavity of the printing device is sealed, the purity of the inert gas is ≥99.99%, the oxygen content inside the cavity is less than 100 ppm, and the selected laser diameter is 60 μm.

[0021] In the present disclosure and possible embodiments, after the layer-by-layer printing is completed, the obtained 3D printed tin-antimony alloy is air-cooled to room temperature.

[0022] In the second aspect, the tin-antimony alloy is prepared by the 3D printing method described in the first aspect.

[0023] The present invention has the following beneficial effects:

[0024] (1) The present invention adopts SLM technology to directly use Sn powder and Sb powder as raw materials to 3D print tin-antimony alloy, which can prepare tin-antimony alloy in large quantities and at low cost, making SLM technology of great significance in the field of preparing binary alloys, thereby broadening the preparation methods of related materials;

[0025] (2) The present invention uses different process parameters from the main body to print the lower surface, so that the mixed powder and the substrate are directly melted and formed, which can be used to directly print the bearing shell part on the bearing liner, and has obvious technical advantages.

[0026] (3) Compared with the cast tin-based babbitt alloy, the present invention adopts the SLM technology to prepare the tin-antimony alloy, which can reduce the grain size of the tin-antimony alloy.

[0027] (4) Compared with the cast tin-based babbitt alloy, the tin-antimony alloy prepared by the SLM technology in the present invention has high hardness, strong resistance to plastic deformation, and good friction and wear performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, and these drawings show embodiments consistent with the present disclosure, and together with the specification, are used to illustrate the technical solutions of the present disclosure:

[0029] Figure 1 The upper surface, lower surface and main structure diagram of the tin-antimony alloy formed part in Example 1;

[0030] Figure 2 The short straight line scanning strategy and scanning angle of the tin-antimony alloy in Example 1;

[0031] Figure 3 a and b are the grain size comparison diagrams of Example 1 and Comparative Example, respectively, where: a. Example 1 (60W-0.6m / s); b. Comparative Example 1;

[0032] Figure 4 The tin-antimony alloy grains under different process parameters in Example 1;

[0033] Figure 5 The chain grains of the columnar grain boundary of Example 1;

[0034] Figure 6a , 6b , 6c, 6d are respectively the tensile stress-strain curves of the tin-antimony alloy under different parameters in Example 1; wherein, 6a is a laser power of 40W and a scanning rate of 0.3-0.7m / s; 6b is a laser power of 50W and a scanning rate of 0.3-0.7m / s; 6c is a laser power of 60W and a scanning rate of 0.3-0.7m / s; 6d is a laser power of 70W and a scanning rate of 0.3-0.7m / s;

[0035] Figure 7 This is the contact form of the friction pair in the friction performance test of the alloys in Example 1 and Comparative Example 1.

[0036] Figure 8 In the figure, a, b, c, and d are respectively the comparison of the friction coefficient curves of Example 1 and Comparative Example 1, wherein: a is dry friction, the loading force is 50N, the rotation speed is 1200r / min, and the time is 30min; b, c, and d are oil friction, the loading forces are 50N, 100N, and 200N, the rotation speed is 1200r / min, and the time is 240min. DETAILED DESCRIPTION

[0037] The present disclosure is described below based on embodiments, but it is worth noting that the present disclosure is not limited to these embodiments. In the detailed description of the present disclosure below, some specific details are described in detail. However, for the parts that are not described in detail, those skilled in the art can also fully understand the present disclosure.

[0038] Furthermore, unless the context clearly requires otherwise, throughout the specification and claims, the words "include," "comprises," and similar words should be interpreted in an inclusive sense rather than an exclusive or exhaustive sense; that is, in the sense of "including but not limited to."

[0039] The study found that when SLM technology is used to prepare tin-based babbitt alloy, when the input energy is too high, the Cu6Sn5 phase in the formed part will grow too large; when the input energy is too low, a large number of unfused defects will be generated in the formed part; due to the single scanning angle of the formed part, the tensile strength of the formed part in different directions varies greatly, thus affecting the mechanical properties of the tin-based babbitt alloy.

[0040] The present application designs a method for 3D printing tin-antimony alloy based on the above research findings, and its main design concept is: using SLM technology to directly prepare tin-antimony alloy from Sn powder and Sb powder, avoiding the process of preparing tin-antimony alloy powder, which can effectively solve the problem of excessive growth of Cu6Sn5 phase when the input energy is too high, resulting in a decrease in mechanical properties; in addition, the layer-by-layer scanning angle for layer-by-layer printing, except for the area that cannot be selected, is executed according to the inter-layer scanning path angle of 10° to 30°, and the inter-layer scanning path angle represents the scanning angle difference between the current layer and the lower layer. The existence of this scanning angle difference can avoid the anisotropy of tensile strength in different directions of the formed part due to the single scanning angle; moreover, using different printing parameters on the lower surface of the formed part can avoid tinning treatment of the substrate, thereby preparing a tin-antimony alloy with higher density and better comprehensive mechanical properties, which meets the mechanical property requirements of tin-based bearing alloys for bearing materials.

[0041] Based on the above design concept, the present disclosure provides a corresponding technical solution for the 3D printing method of the tin-antimony alloy, which is as follows:

[0042] 1. Alloy raw materials:

[0043] The raw materials of the tin-antimony alloy are Sn powder and Sb powder. The average particle diameters of the two metal powders are both 15-50 μm, and more than 95% of the powder particles are spherical or quasi-spherical.

[0044] The Sn powder and Sb powder were placed in a vacuum drying oven for drying respectively, and then mechanically mixed in a vacuum mixer to obtain metal powder for 3D printing. The mixing time was 7 hours. The Sb powder content in the mixed powder was 15%wt, and the rest was Sn powder.

[0045] 2. Printing process:

[0046] The three-dimensional model of the formed part is sliced. The formed part is laid out in a printing device with an inert gas, and powder printing is performed according to the slice data and layout position of the three-dimensional model of the formed part to obtain a 3D printed tin-antimony alloy product using Sn powder and Sb powder as raw materials; the specific process steps are as follows:

[0047] (1) Selective laser melting (SLM) technology is used for 3D printing. The printing equipment is a conventional SLM printing equipment in the art, including a laser device, a forming cylinder and a material cylinder.

[0048] (2) During printing, the forming cavity is sealed, and the inert gas introduced is high-purity argon (purity ≥ 99.99%). After the oxygen content inside the cavity is lower than 100 ppm, the selected laser diameter is 60 μm.

[0049] (3) Print layer by layer according to the three-dimensional model of the formed part. First, the lower surface where the formed part contacts the substrate (316 stainless steel) is powder-printed, and then the main body and upper surface of the formed part are powder-printed.

[0050] During printing, the lower surface of the formed part is 5 layers, and the printing parameters are set to laser power 80W, scanning rate 0.2m / s, printing layer thickness 20μm, scanning spacing 50μm, and scanning strategy short straight line ( Figure 2 );

[0051] The printing parameters for the main body and upper surface of the formed part are set as follows: laser power of 40-60W, scanning rate of 0.3-0.7m / s, printing layer thickness of 40μm, scanning spacing of 80μm, scanning strategy of short straight line, layer-by-layer scanning angles of 20°, 40°, 60°, 120°, 140° and 160°; the upper surface is 5 layers and laser remelting treatment is performed. The main body part depends on the height of the formed part, the printing layer thickness and the number of upper and lower surface layers, and the number of powder layers is determined according to the slicing data.

[0052] (4) After obtaining the 3D printed tin-antimony alloy using Sn powder and Sb powder as raw materials, air cooling is performed to room temperature.

[0053] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and examples.

[0054] In the present invention, unless otherwise specified, the printing materials used are commercially available products well known to those skilled in the art.

[0055] Example 1

[0056] In this embodiment, 3D printing of tin-antimony alloy is performed according to the disclosed method, and the specific process is as follows:

[0057] 1. Alloy raw materials:

[0058] The raw materials of the tin-antimony alloy are Sn powder and Sb powder. The average particle diameters of the two metal powders are both 15-50 μm, and more than 95% of the powder particles are spherical or quasi-spherical.

[0059] The Sn powder and Sb powder were placed in a vacuum drying oven for drying respectively, and then mechanically mixed in a vacuum mixer to obtain metal powder for 3D printing. The mixing time was 7 hours. The content ratio of Sb powder in the mixed powder was 15%wt, and the rest was Sn powder.

[0060] 2. Printing process:

[0061] (1) The mixed powder is added into the forming chamber of the Easy Plus 3D EP-M150 equipment, and high-purity argon gas (purity ≥ 99.99%) is introduced. When the oxygen content in the cavity is lower than 100 ppm, a laser diameter of 60 μm is selected.

[0062] (2) Powder printing is performed based on the 3D model of the part, and the upper and lower surfaces are scanned layer by layer for 5 times.

[0063] (3) First, powder printing is performed on the lower surface and substrate of the molded part, and the printing parameters are set to laser power 80W, scanning rate 0.2m / s, printing layer thickness 20μm, and scanning spacing 50μm. Then, powder printing is performed on the main body and upper surface of the molded part, and the printing parameters are set to laser power 40-70W, scanning rate 0.3-0.7m / s, printing layer thickness 40μm, and scanning spacing 80μm. Among them, the upper surface has 5 layers and is laser remelted. The overall scanning strategy of the molded part is a short straight line, and the scanning angles of each layer are 20°, 40°, 60°, 120°, 140° and 160° ( Figure 1 ).

[0064] (4) After printing is completed to obtain the 3D printed tin-antimony alloy using Sn powder and Sb powder as raw materials, it is air-cooled to room temperature to finally obtain the 3D printed tin-antimony alloy product using Sn powder and Sb powder as raw materials of Example 1.

[0065] Comparative Example 1

[0066] This comparative example is carried out by preparing tin-based babbitt alloy according to the following method, which is as follows:

[0067] Put the tin-based babbitt alloy ZSnSb11Cu6 into an ultrasonic cleaner and add anhydrous ethanol to clean it for 180 seconds. After cleaning, blow it dry with an air gun and put it into a graphite crucible. Put the graphite crucible into the heating ring of the vacuum induction furnace, and fix the graphite mold on the circular platform below the vacuum induction furnace. Pass the inert gas high-purity argon (purity ≥ 99.99%) into the vacuum melting furnace. Start heating and melting at a temperature of 1171K until the babbitt alloy melts. Turn the operating lever to cast the hot molten tin-based babbitt alloy liquid into the graphite mold. After cooling, the tin-based babbitt alloy is obtained.

[0068] The performance of the samples of Example 1 and Comparative Example 1 is compared below. The specific performance comparison method and results are as follows:

[0069] 1. Grain size test

[0070] The microstructure was characterized and the grain size was measured using a Phenom XL scanning electron microscope (SEM). The specific grain size results are shown in Table 1:

[0071] Table 1 Average grain size of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0072]

[0073]

[0074] The results show that the grain size of the cast tin-based babbitt alloy is much larger than that of the SLM tin-antimony alloy sample. Due to the characteristics of SLM technology, the laser acts on the powder bed, and the Sn powder and Sb powder are melted into a molten pool very quickly for reaction. The molten pool solidifies at a very fast speed, which increases the supercooling of the tin-antimony alloy. As the supercooling increases, a large number of crystal nuclei will be generated inside the molten pool. During the growth process, the crystal nuclei solidify too quickly, and the grain size decreases accordingly, so they are dispersed in the matrix. For details, see Figure 3 and Figure 4 .

[0075] like Figure 3 As shown in the figure, there are two types of grains in the cast tin-based babbitt alloy: block-shaped and needle-shaped. The grains of the SLM tin-antimony alloy are mostly irregular polygons. The grain size of the cast tin-based babbitt alloy is much larger than that of the SLM tin-antimony alloy, and a large number of grains in the SLM tin-antimony alloy are dispersed on the matrix.

[0076] like Figure 4 As shown in Figure 2, with the increase of laser power, the average grain size of SLM tin-antimony alloy increases, and with the increase of scanning speed, the average grain size decreases.

[0077] In addition, if Figure 5 As shown in Figure 1, in the tin-antimony alloy, the second phase grains will precipitate and grow along the grain boundaries of the columnar crystals and form a chain morphology. The second phase grains can reduce the movement of dislocations inside the columnar crystals and reduce the degradation of material properties caused by the grain orientation of the columnar crystals.

[0078] 2. Density test

[0079] The density test was carried out using the Archimedes drainage method. The sample size was a block of 10mm×10mm×10mm. The specific test results are shown in Table 2:

[0080] Table 2 Density of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0081]

[0082]

[0083] The results show that the density of SLM tin-antimony alloy is higher than that of cast tin-based babbitt alloy. The reason is that the second phase grains in cast tin-based babbitt alloy are larger, which causes cracking due to stress during the subsequent solidification process. Gas is also involved in the casting process, causing the density to decrease. This reduces the mechanical properties. The grains of SLM tin-antimony alloy are small and are less affected by stress. Appropriate SLM process parameters can reduce element segregation and defects inside the tin-antimony alloy and increase the density.

[0084] 3. Brinell hardness test

[0085] The Brinell hardness was measured using a 320HBS-3000 digital Brinell hardness tester, with a load of HBW10 / 500 and a holding time of 10s. The specific test results are shown in Table 3 below:

[0086] Table 3 Brinell hardness of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0087]

[0088] The results show that the hardness of SLM tin-antimony alloy is higher than that of cast tin-based babbitt alloy. That is, the hardness of SLM tin-antimony alloy is greater than that of cast tin-based babbitt alloy. The reason is that the grains of SLM tin-antimony alloy are fine and dispersed in the matrix, and the load transferred by the grains will be more evenly distributed. Fine grain strengthening and dispersion strengthening can not only improve the strength of tin-antimony alloy, but also improve its plasticity and toughness. The density of tin-antimony alloy is improved, which increases the plastic deformation resistance of tin-antimony alloy, thereby improving the Brinell hardness.

[0089] 4. Tensile performance test

[0090] The tensile specimen size that meets GB / T228.1-2021 is cut by DK77 electric spark wire cutting machine. The tensile strength test is carried out by DNS-100 electronic universal testing machine, with the tensile load pointing vertically to the ground and the tensile strain rate being 0.5mm / min. The specific test results are shown in Table 4, Table 5 and Figure 6 below:

[0091] Table 4 Tensile strength of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0092]

[0093] Table 5 Elongation of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0094]

[0095] The results show that the tensile strength and elongation of SLM tin-antimony alloy are both higher than those of cast tin-based babbitt alloy. The fast melting and solidification characteristics of SLM technology make the tin-antimony alloy have high dislocation density and small grains, which means that the grain boundaries in the tin-antimony alloy increase. When the external loading force increases, the grain boundaries will produce greater resistance to dislocation movement during deformation, playing a role in dislocation strengthening; the refined and dispersed grains increase the strength of the tin-antimony alloy, so the tin-antimony alloy prepared by SLM has improved elongation and tensile strength.

[0096] Figure 6 shows the tensile stress-strain curves of the tin-antimony alloy in Example 1 under different parameters. As shown in Figure 6, with the increase of laser power, the tensile strength of the SLM tin-antimony alloy first increases and then decreases; with the increase of scanning speed, the tensile strength of the SLM tin-antimony alloy first increases and then decreases. When the laser power is 60W and the scanning speed is 0.6m / s, the maximum tensile strength is 87.72MPa. When the laser power is 50W and the scanning speed is 0.5m / s, the maximum elongation is 30.58%.

[0097] 5. Friction performance test

[0098] The friction performance test was carried out using the MMW-100A multifunctional friction and wear testing machine, specifically the friction and wear test between metals. During the test, the contact form of the friction pair was as follows: Figure 7 The pin-disc type shown. In Example 1, a sample of 60W-0.6m / s was selected for testing. QT50-5 ductile iron was selected as the friction pair, the dry friction loading force was 50N, the speed was 1200r / min, and the time was 30min. The oil friction loading force was 50N, 100N and 200N, the speed was 1200r / min, and the time was 240min. The specific test results are shown in Tables 6, 7 and Figure 8 :

[0099] Table 6 Average friction coefficient of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0100]

[0101] Table 7 Friction amount of the tin-antimony alloy of Example 1 and the tin-based babbitt alloy of Comparative Example 1

[0102]

[0103] The results show that the friction and wear performance of the SLM tin-antimony alloy of Example 1 is better than that of the cast tin-based babbitt alloy of Comparative Example 1. The reason is that the SLM tin-antimony alloy of Example 1 is prepared with Sn powder and Sb powder as raw materials using the SLM technology. The fast melting and fast solidification characteristics of the SLM technology result in a fine hard phase structure in the tin-antimony alloy. Due to the finite element / discrete forming principle of the SLM forming technology, the hard phase is evenly distributed, the hardness of the tin-antimony alloy is relatively high, and there are tiny pores in the formed parts, which can be used as oil storage channels in an oil-lubricated state. During the friction process, when the load is small, the hard phase structure in the tin-antimony alloy is fine, so the wear debris is even finer. The wear debris remaining between the friction pairs can act as a ball, reducing the amount of wear and the friction coefficient. The stress generated during the friction process is small, and it is not easy to produce cracks with the matrix. During the wear period, a small part of the abrasive particles will fill the spalling pits, avoiding the damage of friction heat to the material and extending the service life of the material.

[0104] Depend on Figure 8 It can be seen that under dry friction conditions, the friction coefficient curve of the tin-based babbitt alloy is higher than that of the SLM tin-antimony alloy. Under oil friction conditions, when the load is 50N, the friction coefficient curve of the SLM tin-antimony alloy is more stable than that of the tin-based babbitt alloy; when the load is 100N, the friction coefficient curve of the tin-based babbitt alloy begins to fluctuate regularly, and the friction coefficient curve of the SLM tin-antimony alloy is still stable; when the load is 200N, the friction coefficient curves of the tin-based babbitt alloy and the SLM tin-antimony alloy are wavy. However, the friction coefficient curve of the SLM tin-antimony alloy is lower, that is, the friction coefficient is small.

[0105] It can be seen from the above performance test results that compared with the cast tin-based babbitt alloy, the density of the tin-antimony alloy prepared by the SLM technology of the present invention is increased, the hardness is increased, the tensile strength is strengthened, the wear resistance is increased, and the service life is extended. At the same time, the process of preparing the tin-antimony alloy powder in the early stage is reduced, energy is saved, and costs are reduced.

[0106] The embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A 3D printing method for tin-antimony alloy, characterized in that: include: Printing layer by layer according to the three-dimensional model of the formed part, wherein the layer by layer printing uses a mixed powder composed of Sn powder and Sb powder; The layer-by-layer scanning angle of the layer-by-layer printing is performed according to the layer-by-layer scanning path angle of 10° to 30°, except for the area that cannot be selected.

2. The 3D printing method of tin-antimony alloy according to claim 1, characterized in that: The particle size of the mixed powder is 15 μm to 50 μm, wherein more than 95% of the powder particles are spherical or quasi-spherical; and / or, The content of the Sb powder in the mixed powder is 15%wt, and the rest is the Sn powder; and / or, The Sn powder and the Sb powder are vacuum dried respectively and then vacuum mechanically mixed to obtain the mixed powder.

3. The 3D printing method of tin-antimony alloy according to claim 1 or 2, characterized in that: The order of layer-by-layer printing is to first perform powder printing on the lower surface of the molded part in contact with the substrate, and then perform powder printing on the main body and the upper surface of the molded part.

4. The 3D printing method of tin-antimony alloy according to claim 3, characterized in that: The lower surface is 4-6 layers, and the upper surface is 4-6 layers and is laser remelted; The inter-layer scanning path has an angle of 20°.

5. The 3D printing method of tin-antimony alloy according to claim 4, characterized in that: The printing parameters for powder printing on the lower surface are set as follows: laser power 80W, scanning rate 0.2m / s, layer thickness 20μm, scanning spacing 50μm, and scanning strategy short straight line; The printing parameters for powder printing on the main body and the upper surface of the formed part are set as follows: laser power of 40-60 W, scanning rate of 0.3-0.7 m / s, layer thickness of 40 μm, scanning spacing of 80 μm, and scanning strategy of short straight line.

6. The 3D printing method of tin-antimony alloy according to claim 1, 2, 4 or 5, characterized in that: The layer-by-layer printing is performed using a selective laser melting technology.

7. The 3D printing method of tin-antimony alloy according to claim 6, characterized in that: The method for printing layer by layer according to the three-dimensional model of the formed part comprises: The three-dimensional model of the molded part is sliced, the molded part is laid out in a printing device into which an inert gas is introduced, and powder printing is performed according to the slice data and layout position of the three-dimensional model of the molded part.

8. The 3D printing method of tin-antimony alloy according to claim 7, characterized in that: When performing the powder printing, the forming cavity of the printing device is sealed, the purity of the inert gas is ≥99.99%, the oxygen content in the cavity is lower than 100 ppm, and the selected laser diameter is 60 μm.

9. The 3D printing method of tin-antimony alloy according to claim 1, 2, 4, 5, 7 or 8, characterized in that: After the layer-by-layer printing is completed, the obtained 3D printed tin-antimony alloy is air-cooled to room temperature.

10. A tin-antimony alloy, characterized in that: The preparation method thereof is: The 3D printing method according to any one of claims 1 to 9 is adopted.